The Incipient Motion Features of Sediment from Yangtze Estuary: Annular Flume Experiments - Wei, Huang (Sci Rep, 2017)
In this study, annular flume experiments are carried out, using the sediment samples collected from Yangtze estuary. The incipient velocity and the incipient shear stress of three different groups of median grain size of sediment are given. The turbulent kinetic energy method (TKE) is used to determine the bed shear stress (τ), by evaluating variations in the suspended sediment concentration (SSC) within the water column. The suspended sediment concentration increases with the increase of the bed shear stress. When the sediment concentration reaches a certain concentration, the rate of change in τ obviously slows down. As the concentration increasing again, the bed shear stress grows rapidly with different growth rate attributed to different grain size. The results of the experiments indicate that SSC and grain size have strong influence on τ.